2022
DOI: 10.1007/s12528-022-09342-1
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging learning experience design: digital media approaches to influence motivational traits that support student learning behaviors in undergraduate online courses

Abstract: Higher education may benefit from investigating alternative evidence-based methods of online learning to understand students’ learning behaviors while considering students’ social cognitive motivational traits. Researchers conducted an in situ design-based research (DBR) study to investigate learner experience design (LXD) methods, deploying approaches of asynchronous video, course dashboards, and enhanced user experience. This mixed-methods study (N = 181) assessed associations of students’ social cognitive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Notably, three papers were published in 2022 (Winstone, 2022;Ellis, 2022;Popov et al, 2022). The year 2023 saw a significant increase, with 21 papers highlighting a growing number of researchers focusing on the culture of learning and its various components (Balleisen et al, 2023;Culver et al, 2023;Dziubaniuk et al, 2023;Davis et al, 2023;Tan, 2023;Wong et al, 2023;Xie et al, 2023;Culver, 2023;Romeiro et al, 2023;Heng, 2023;Madanat et al, 2023;Durão et al, 2023;Myllykoski-Laine et al, 2023;Mutale et al, 2023;Vu et al, 2023;Burkhalter, 2023;Müller, 2023;Dammery et al, 2023). Furthermore, four papers published at the beginning of 2024 indicate a continuing interest in the research theme Xu, 2024;Sörensen et al, 2024).…”
Section: Demographics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, three papers were published in 2022 (Winstone, 2022;Ellis, 2022;Popov et al, 2022). The year 2023 saw a significant increase, with 21 papers highlighting a growing number of researchers focusing on the culture of learning and its various components (Balleisen et al, 2023;Culver et al, 2023;Dziubaniuk et al, 2023;Davis et al, 2023;Tan, 2023;Wong et al, 2023;Xie et al, 2023;Culver, 2023;Romeiro et al, 2023;Heng, 2023;Madanat et al, 2023;Durão et al, 2023;Myllykoski-Laine et al, 2023;Mutale et al, 2023;Vu et al, 2023;Burkhalter, 2023;Müller, 2023;Dammery et al, 2023). Furthermore, four papers published at the beginning of 2024 indicate a continuing interest in the research theme Xu, 2024;Sörensen et al, 2024).…”
Section: Demographics Of the Included Studiesmentioning
confidence: 99%
“…Sustainable practices in online education are essential for long-term success, emphasizing the need for teaching methods that can adapt to and thrive in digital environments (Dziubaniuk et al, 2023). Utilizing evidence-based methods for online learning can significantly improve educational outcomes by ensuring that instructional strategies are grounded in solid research (Wong et al, 2023). Additionally, effective teaching methods that integrate career development learning (CDL) enhance students' perceived employability (SPE), thereby improving their career prospects .…”
Section: Effectiveness Of Teaching / Learning Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wong, Joseph [155] , Zooming in or Zoning Out: Examining Undergraduate Online Learning Experiences with Zoom and the Role of Mind-Wandering, Dryad, Dataset, https://doi.org/10.7280/D1GT32…”
Section: Dataset Accessmentioning
confidence: 99%
“…Teachers need active and fun learning media to engage students in learning (Puspitarini & Hanif, 2019). Another study showed the significant positive influence of learning media and parental attention on students' learning motivation (Wong & Hughes, 2022).…”
Section: Introductionmentioning
confidence: 99%